Spanish adaptation of the stepparent role strain index - Espinar Fellmann, Isabel; Carrasco Galán, María José; Muñoz San Roque, Isabel; Carrasco Galán, Inés (The Spanish Journal of Psychology, 2008)
Stepparent role strain refers to the fragile position of these family members in stepfamilies due to the lack of clear social expectations about their roles. This ambiguity facilitates family conflict and a lack of stepparents’ integration into the family system. The aim of this paper is to adapt a pioneer measure of stepparent role strain—the Stepparent Role Strain Index of Whitsett and Land (1992)—in a Spanish sample and to analyze its construct validity. The final instrument is made up of 26 items which have good internal consistency (α= .89) and an underlying six-factor structure, explaining 64.50% of the total variance.